2013
DOI: 10.1186/1472-6882-13-369
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of allergic airway hyperresponsiveness and remodeling in mice by Astragaliradix Antiasthmatic decoction

Abstract: BackgroundAstragali radix Antiasthmatic Decoction (AAD), a traditional Chinese medication, is found effective in treating allergic diseases and chronic cough. The purpose of this study is to determine whether this medication could suppress allergen-induced airway hyperresponsiveness (AHR) and remodeling in mice, and its possible mechanisms.MethodsA mouse model of chronic asthma was used to investigate the effects of AAD on the airway lesions. Mice were sensitized and challenged with ovalbumin (OVA), and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In this study, there was a significant recovery of goblet cell hyperplasia, thickness of the collagen layer, and the VEGF signaling pathway in BAW-treated groups. These findings are similar to those of previous in vivo studies in which numerous natural products, including Vitex rotundifolia L. [ 41 ], Astragali radix Anti-Asthmatic Decoction [ 42 ], Bangpungtongseong-san [ 43 ], and Suhuang antitussive capsule [ 44 ], were reported to induce the stimulation of airway remodeling in OVA-treated BALB/c mice. However, the preventive effects of fermented natural products against airway remodeling have never been investigated in an OVA-induced asthma model.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, there was a significant recovery of goblet cell hyperplasia, thickness of the collagen layer, and the VEGF signaling pathway in BAW-treated groups. These findings are similar to those of previous in vivo studies in which numerous natural products, including Vitex rotundifolia L. [ 41 ], Astragali radix Anti-Asthmatic Decoction [ 42 ], Bangpungtongseong-san [ 43 ], and Suhuang antitussive capsule [ 44 ], were reported to induce the stimulation of airway remodeling in OVA-treated BALB/c mice. However, the preventive effects of fermented natural products against airway remodeling have never been investigated in an OVA-induced asthma model.…”
Section: Discussionsupporting
confidence: 91%
“…One possible reason could be the presence genetically dominant Th2 immune responses in BALB/c mice. [31][32][33] Moreover, Th2-produced IL-4 induces asthma features including recruitment of inflammatory cells into the airways and bronchial inflammation 3,5,30,34 In our experiment, OVA mice showed higher levels of Th2related cytokine IL-4, total WBC number and eosinophil percentages and obvious peribronchial inflammation compared to normal non-sensitized mice which confirmed an effective asthma modeling. However, lymphocyte percentage in OVA control animals was reduced compared to normal control animals (Figure 2C).…”
Section: Discussionsupporting
confidence: 69%
“…IL-13 was reported to be the crucial mediator in eosinophil induced airway AHR and mucus production 16 23 24 . Previous studies including our investigations found that IL-13 down-regulation remit airway inflammation and AHR, as well as mucus production 25 26 . In our present study, we observed a significantly decreased IL-13 level in lung homogenates of Suhuang treatment groups, which should contribute to the overall protective effects in the asthma model.…”
Section: Discussionmentioning
confidence: 48%
“…TGF-β1 also induces proliferation, survival and extracellular matrix (ECM) secretion in ASMCs, suggesting a possible cause of increased thickness of airway tissues 15 . Inhibition of TGF-β1 including with traditional Chinese medicine could improve asthmatic symptom 26 31 32 33 . We demonstrated that Suhuang effectively attenuated TGF-β1 expression induced by chronic allergen exposure.…”
Section: Discussionmentioning
confidence: 99%